Does the Locally-Adaptive Model of Archaeological Potential (LAMAP) work for hunter-gatherer sites? A test using data from the Tanana Valley, Alaska - Rondeau, Rob; Carleton, W. Christopher; Collard, Mark; Driver, Jonathan (PLOS ONE, 2022)
We report an assessment of the ability of the Locally-Adaptive Model of Archaeological Potential (LAMAP) to estimate archaeological potential in relation to hunter-gatherer sites. The sample comprised 182 known sites in the Tanana Valley, Alaska, which was occupied solely by hunter-gatherers for about 14,500 years. To estimate archaeological potential, we employed physiographic variables such as elevation and slope, rather than variables that are known to vary on short time scales, like vegetation cover. Two tests of LAMAP were carried out. In the first, we used the location of a random selection of 90 sites from all time periods to create a LAMAP model. We then evaluated the model with the remaining 92 sites. In the second test, we built a LAMAP model from 12 sites that pre-date 10,000 cal BP. This model was then tested with sites that post-date 10,000 cal BP. In both analyses, areas predicted to have higher archaeological potential contained higher frequencies of validation sites. The performance of LAMAP in the two tests was comparable to its performance in previous tests using archaeological sites occupied by agricultural societies. Thus, the study extends the use of LAMAP to the task of estimating archaeological potential of landscapes in relation to hunter-gatherer sites.